Fine‐Scale Genetic Structure of Small Fish Populations in Islands: The Case of Brook Charr Salvelinus fontinalis (Mitchill, 1814) in Saint‐Pierre and Miquelon (France) - Julie Viana; Guillaume Evanno; Céline Audet; Fabrice Teletchea (Evolutionary Applications)
ABSTRACT Island ecosystems, particularly vulnerable to environmental challenges, host many endangered native species. Diadromous fish, in particular, are threatened throughout their marine and freshwater habitats. The conservation of these species requires an in‐depth understanding of their genetic diversity and structure, to better understand their adaptive potential. We investigated fine‐scale population diversity and structure in native brook charr (Salvelinus fontinalis) by genotyping 10 microsatellite loci in 244 individuals at three spatial scales in Saint‐Pierre and Miquelon, France. We found limited genetic variability across the archipelago, with particularly low genetic diversity in one island, Langlade. A significant difference in allelic richness was also detected among the three islands, indicating a difference in genetic composition across the archipelago, probably induced by historical stocking actions on both Saint‐Pierre and Miquelon. Finally, a strong genetic structure was detected across the archipelago among hydrosystems (overall FST = 0.19) and even within several of them. The presence of predominant interisland gene flow combined with complete genetic isolation from certain hydrosystems suggests that this contemporary genetic structure is the result of both natural demographic processes during the species postglacial colonization and recent restocking actions. The complex genetic structure of such isolated brook charr subpopulations highlights the importance of considering fine‐scale genetic structure in conservation management.